1999
DOI: 10.1086/314726
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Reproducible Method for Collecting Nasal Secretions in Frail Elderly Adults, for Measurement of Virus‐Specific IgA

Abstract: The standard method for collection of respiratory secretions, by use of a nasal wash (NW) to measure virus-specific IgA, is problematic in frail elderly adults. Therefore, a simplified collection approach using a nasal swab (NS) is described. NW and NS samples were collected from healthy young and frail elderly adults, and IgA titers to respiratory syncytial virus (RSV) fusion and attachment glycoproteins were determined by enzyme immunoassay. Correlation between IgA titers in NW and NS was excellent for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In RSV, serum neutralising antibody titres have been shown to negatively correlate with risk of medical attendance with RSV disease but no upper threshold of protection has been identifiable, with serum neutralising antibodies only broadly dividing individuals into those with minimal antibody (and therefore highly susceptible) and those with adult-like levels [39]. Previous observational studies indicated that local RSV-specific antibodies might be better correlates of protection but suggested that protective antibody levels were not well maintained [40,41]. To address these questions, we used the experimental human infection system to study the relationship between pre-existing local and systemic antibodies with infection [42].…”
Section: Experimental Challenge Provides Insights Into Pathogenesismentioning
confidence: 99%
“…In RSV, serum neutralising antibody titres have been shown to negatively correlate with risk of medical attendance with RSV disease but no upper threshold of protection has been identifiable, with serum neutralising antibodies only broadly dividing individuals into those with minimal antibody (and therefore highly susceptible) and those with adult-like levels [39]. Previous observational studies indicated that local RSV-specific antibodies might be better correlates of protection but suggested that protective antibody levels were not well maintained [40,41]. To address these questions, we used the experimental human infection system to study the relationship between pre-existing local and systemic antibodies with infection [42].…”
Section: Experimental Challenge Provides Insights Into Pathogenesismentioning
confidence: 99%
“…The titer of nasal IgA to F, Ga, and Gb was determined using published methods (23). Total protein in each nasal sample was determined (Micro BCA, Rockford, IL) and nasal IgA was corrected to a total protein of 100 g/ml.…”
Section: Rsv Serologymentioning
confidence: 99%
“…During enrollment, before the RSV season, demographic and medical information was recorded, and a blood and nasal swab sample was obtained for the determination of antibodies. The nasal-swab sample for antibody was obtained by rotating a moistened cottontipped swab for 5 s in the anterior nares, at the level of the turbinates, and eluted into 3 mL of sterile saline [10]. Samples were frozen at Ϫ80ЊC until analysis.…”
Section: Study Subjects and Illness Surveillancementioning
confidence: 99%